2015
DOI: 10.1063/1.4922057
|View full text |Cite
|
Sign up to set email alerts
|

Reconnection dynamics with secondary tearing instability in compressible Hall plasmas

Abstract: The dynamics of a secondary tearing instability is systematically investigated based on compressible Hall magnetohydrodynamic. It is found that in the early nonlinear phase of magnetic reconnection before onset of the secondary tearing instability, the geometry of the magnetic field in the reconnection region tends to form a Y-type structure in a weak Hall regime, instead of an X-type structure in a strong Hall regime. A new scaling law is found that the maximum reconnection rate in the early nonlinear stage i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 23 publications
1
17
0
1
Order By: Relevance
“…Particularly for the ion inertial length d a i =1.0, the maximum reconnection rate is even one order larger than that without the Hall effect. These results agree well with that from the previous Hall MHD simulations [11,39,40]. Thus, different reconnection rates can be obtained by a change in the ion inertial length.…”
Section: Simulation Resultssupporting
confidence: 92%
“…Particularly for the ion inertial length d a i =1.0, the maximum reconnection rate is even one order larger than that without the Hall effect. These results agree well with that from the previous Hall MHD simulations [11,39,40]. Thus, different reconnection rates can be obtained by a change in the ion inertial length.…”
Section: Simulation Resultssupporting
confidence: 92%
“…It has a potential importance of understanding the dynamics of reconnection current sheets that there are considerably different chaos-induced resistivity in the different types of chaos regions in reconnection current sheets. A lot of investigations have shown that an initial reconnection current sheet with the double Y-type magnetic configuration usually is unstable against the resistive tearing mode, especially in high-temperature plasmas such as the solar corona (Sato 1979;Ugai 1984;Schumacher & Kliem 1996;Nitta 2007;Ma et al 2015Ma et al , 2018Wang et al 2017;Lu et al 2018;Xia & Zharkova 2018). This may lead to the formation of a magnetic island, which has an O-type neutral point at its center and two X-type neutral points at its two sides, between the two Y-type neutral points, and then the magnetic island further collapses to a new current sheet with the double Y-type configuration.…”
Section: Resultsmentioning
confidence: 99%
“…Investigations on the dynamics of reconnection current sheets (Sato 1979;Ugai 1984;Schumacher & Kliem 1996;Nitta 2007;Ma et al 2015Ma et al , 2018Wang et al 2017;Lu et al 2018;Xia & Zharkova 2018) showed that the dynamical process has remarkably localized and inhomogeneous characteristics, in which the enhancements of current and dissipation occurs, respectively, near the O-type and the X-type neutral points in the reconnection current sheet. In particular, this implies that the anomalous resistivity should have an inhomogeneous distribution in the reconnection current sheet, and hence that a reasonable generation mechanism for the anomalous resistivity should could lead to higher and lower anomalous resistivity near the O-type and X-type neutral points, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that a thin current sheet forms during magnetic reconnection and may be unstable to the secondary tearing instability when the plasma resistivity is sufficiently low [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The secondary tearing instability in the thin current sheets might lead to fast reconnection phenomena both in space [2,3,5,[15][16][17][18][19][20][21][22][23][24] and Tokamak plasma [25][26][27][28][29][30][31][32][33]. During the development of secondary tearing instabilities, current sheets break up, and multiple X-point reconnection occurs [34], which results in the formation of multiple secondary islands or the so-called 'plasmoids'.…”
Section: Introductionmentioning
confidence: 99%